Marketing Management Training for UMKM Assisted by Baznas Microfinance Village (BMD) Gunungsari - Herdiana Fitriani; Taufik Samsuri; I wayan Karmana; Novi Sulastri; M Zaenuddin; Haerazi Haerazi; Aminullah Aminullah; Soemardiawan Soemardiawan; Fitri Anggraini Hariyanto; Muhammad Ikhsan (Sasambo: Jurnal Abdimas (Journal of Community Service), 2023)
Usaha Mikro Kecil Menengah (UMKM) play a strategic role in Indonesia's economic growth, but they still face various obstacles, especially in product marketing. This research aims to identify and address the challenges in marketing the products of UMKM, particularly those under the guidance of Baznas Microfinance in the Gunungsari Village, NTB. The main focus of this research is marketing management training as a solution to enhance the marketing capabilities of UMKM. This research employs a qualitative descriptive approach to collect data through in-depth interviews, observations, and analysis of related documents. The findings indicate that marketing constraints for UMKM involve a lack of human resources understanding effective marketing concepts. Therefore, the Community Service Team initiates marketing management training as a concrete effort to strengthen the marketing capacity of UMKM. The training aims to improve the understanding of UMKM actors regarding marketing strategies, branding, and the application of technology in product promotion. The results of the training are expected to make a positive contribution to the development of UMKM, enhance product competitiveness, and expand market reach. This article provides a systematic, factual, and accurate overview of the role of marketing management training in empowering UMKM. By publishing this article in Lumbung Inovasi, it is hoped to contribute to a broader understanding of UMKM marketing literacy and inspire relevant parties in the development of similar training activities in various regions.